The impact of slope and rainfall on the contaminant transport from mountainous groundwater to the lowland surface water - Xu, Xiaojun; Zhu, Ming; Zhou, Ling; Ma, Mingxia; Heng, Jingmei; Lu, Li; Qu, Weiyi; Xu, Zhongyuan (Frontiers in Environmental Science, 2024)
The surface water and groundwater in mountainous area is vulnerable to the mining and transportation construction in Sichuan Province, China. Pollutants produced by anthropogenic activities transport within the groundwater from mountains to rivers on the plain, bringing contamination to the surface water. This study investigates the process of groundwater flow and contaminant transport from mountains to the lowlands based on synthetic numerical models. Two key factors are considered: precipitation and the slope of the mountain. Based on the real situation in Sichuan Province, four rainfalls are defined as 600, 800, 1000, 1200 mm/yr, and five slope angles are considered: 20°, 25°, 30°, 35°, 40°. The simulation results reveal that the groundwater level and solute transport are strongly influenced by the precipitation amounts and slope angles. The mountains with lower slopes maintain a relatively higher groundwater level under steady-state rainfall conditions, such as groundwater levels decrease from 340 m to 300 m as slope angles increasing under 1200 mm/yr precipitation. Contaminant transport from the source in the mountain to the surface river are faster with increasing precipitations and decreasing slope angles. The model with 20° slope and 1200 mm/yr precipitation exhibits the fastest solute migration, reaching the river in 65 years. And the models with 35° and 40° under 600 mm/yr show the slow transport speed which the arriving time are more than 75 years. In addition, higher precipitation may lead to more contaminant transport to the river.